Interpretation of US cancer statistics 2025 and its implications for cancer prevention and treatment in China - MU Sibo, ZHOU Changming, ZHENG Ying (Zhongguo aizheng zazhi, 2025)
In January 2025, American Cancer Society released the latest cancer statistics, projecting approximately 2 041 910 new cancer cases and 618 120 cancer-related deaths in the United States (U.S.). The cancer mortality rate in the U.S. continues to decline, with a reversal in gender disparities and an increasing cancer burden among middle-aged and young populations. Significant differences in incidence and mortality rates are attributed to variations in population characteristics, intervention screening measures, healthcare accessibility, and policy factors across different regions and populations within the U.S. Compared with the U.S., the cancer spectrum in China is different, and the incidence rates of lung cancer and breast cancer are rapidly rising among young women, with an average annual growth rate exceeding 3%. Infection-related cancer incidence rates are relatively high, with the incidence of gastric cancer, liver cancer and cervix cancer in China being 25.4/105, 26.0/105 and 21.8/105 in 2022 respectively, surpassing U.S. incidence levels. Alarmingly, the cumulative HPV vaccination coverage among eligible Chinese women during 2018-2020 was merely 2.24%, reflecting dual barriers of low screening compliance and inadequate prevention infrastructure. There is a need to further enhance primary cancer prevention and comprehensive risk factor control, prioritize cancer prevention strategies for young and female populations, formulate population-tailored prioritized prevention frameworks and strengthen multi-stakeholder financing mechanisms for personalized screening programs, with the aim of achieving the "Healthy China 2030" cancer prevention and control goals and contributing China's approach to global cancer governance.